Designing an Application for Monitoring and Evaluating the Performance of Public Service Delivery in Garut Regency Using the Rapid Application Development Method - Umamah, Ai; Rahayu, Dinar; Wijaya, Indra (RISTEC : Research in Information Systems and Technology, 2024)
Public services play a pivotal role in assessing the effectiveness of local governance, reflecting the government's commitment to societal welfare, and serving as indicators of bureaucratic transparency and efficiency. This research focuses on the design of an application dedicated to Monitoring and Evaluating the Performance of Public Service Providers (PEKPPP) in Garut Regency using the Rapid Application Development (RAD) approach. The primary objective of this study is to facilitate data collection, performance measurement, and provide improvement recommendations in accordance with prevailing regulations. Through literature review, observation, and interviews, comprehensive data were gathered to understand PEKPPP thoroughly. The RAD approach was adopted for system development, encompassing the stages of Requirements Planning, Design, and Implementation. System design involves the use of Unified Modeling Language (UML) for system modeling and Entity Relationship Diagram (ERD) for database modeling. This research is expected to contribute to enhancing the quality of public services in Garut Regency by providing a tool for efficient data collection, performance measurement, and improvement recommendations. Keywords: application, performance evaluation, RAD